Pathophysiology - Banasik, Jacquelyn L (St. Louis : Elsevier, 2019)
"Pathophysiology includes recent and relevant information on anatomy, biochemistry, cell physiology, genomics, and pathophysiology while not overwhelming the reader with minute detail. Attention is given to major concepts relevant to clinical practice while still providing enough detail for deep understanding"--
Keywords: Pathophysiology